2020
DOI: 10.1038/s41598-020-58827-5
|View full text |Cite
|
Sign up to set email alerts
|

Large-for-gestational-age phenotypes and obesity risk in adulthood: a study of 195,936 women

Abstract: While there is evidence that being born large-for-gestational-age (LGA) is associated with an increased risk of obesity later in life, the data are conflicting. Thus, we aimed to examine the associations between proportionality at birth and later obesity risk in adulthood. This was a retrospective study using data recorded in the Swedish Birth Register. Anthropometry in adulthood was assessed in 195,936 pregnant women at 10-12 weeks of gestation. All women were born at term (37-41 weeks of gestation).LGA was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 48 publications
(59 reference statements)
3
49
0
1
Order By: Relevance
“…On a short-term basis large babies are more likely to suffer from intrapartal asphyxia, hypoglycemia as well as labor and shoulder dystocia. The longterm effects of being born macrosomic and LGA are less clear but some studies have shown an elevated risk of obesity and CVD (Ornoy, 2011, Gu et al, 2012, Derraik et al, 2020 as well as a higher risk for leukemia and Hodgkin's lymphoma (Roman et al, 2013, Crump et al, 2015, Petridou et al, 2015, Triebwasser et al, 2016, Groves et al, 2018. Given the fact that an increasing amount of ART cycles are performed as FET, large scale studies on the long-term effects are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…On a short-term basis large babies are more likely to suffer from intrapartal asphyxia, hypoglycemia as well as labor and shoulder dystocia. The longterm effects of being born macrosomic and LGA are less clear but some studies have shown an elevated risk of obesity and CVD (Ornoy, 2011, Gu et al, 2012, Derraik et al, 2020 as well as a higher risk for leukemia and Hodgkin's lymphoma (Roman et al, 2013, Crump et al, 2015, Petridou et al, 2015, Triebwasser et al, 2016, Groves et al, 2018. Given the fact that an increasing amount of ART cycles are performed as FET, large scale studies on the long-term effects are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…BMI was calculated as weight (kg) divided by height (m) squared [54]. PI was calculated as: weight (g) × 100/(height, cm 3 ) [55,56]. Biiliocristal/biacromial ratio was calculated as biiliocristal breath divided by biacromial breath, both in cm [57].…”
Section: Variables and Instrumentsmentioning
confidence: 99%
“…Derraik et al retrospectively studied 195 936 Swedish women and found that those born LGA by weight, or weight and length combined, had an increased risk for obesity compared with those born AGA (adjusted relative risk 1.40; 95% CI 1.39-1.63 and 1.51; 1.37-1.67, respectively). 18 In contrast, being born LGA by length only was not associated with increased obesity risk. These authors and others have speculated that being born excessively long is genetically driven, whereas, being born excessively heavy is related to in utero factors.…”
Section: Beyond Weight: the Importance Of Changes In Body Compositionmentioning
confidence: 85%
“…This change is in part due to the increased prevalence of maternal obesity and hyperglycemia, which lead to fetal overnutrition. 17,18 Why Weight Is Not Enough Most studies looking at obesity risk have relied on anthropometric measurements such as weight, which does not indicate body size, or the BMI, which may not accurately reflect differences in body composition. Although infants who are born SGA are small, and infants who are born LGA are large, little research has explored how these differences in weight are distributed between the fat-and fat-free mass compartments.…”
Section: Size At Birth and Obesitymentioning
confidence: 99%